Analisis Politik dan Hukum Pemilihan Presiden Secara Langsung - zulfirman zulfirman (Jurnal Hukum IUS QUIA IUSTUM, 2002)
The idea the President election directly by the fpeople is not validated because it contra dicts with the basic political principles (ideal principles, Pancasila) and formal judical principle as expressed on Paragraph 1 article (2) Constitution 1945. In the frame of strengthen for law supremacy it will bee any clash between the political will and the,law desires about President election directly by the People. -